Simple Fluoroscopy-Guided Transforaminal Lumbar Puncture: Safety and Effectiveness of a Coaxial Curved-Needle Technique in Patients with Spinal Muscular Atrophy and Complex Spines - Jacobson, J.P.; Cristiano, B.C.; Hoss, D.R. (American Journal of Neuroradiology, 2020)
SUMMARY: Patients with spinal muscular atrophy often have complete interlaminar osseous fusion, precluding lumbar puncture via the standard interlaminar approach. Recently, we have developed a new coaxial curved-needle variation of fluoroscopy-guided transforaminal lumbar puncture for intrathecal injections in this patient population. Between October 2017 and November 2018, fifty-nine consecutive transforaminal lumbar punctures using this technique were performed in 12 patients with spinal muscular atrophy for intrathecal nusinersen injection, with a 100% technical success rate and no C1–2 punctures required. One major complication occurred, consisting of a post–dural puncture headache, which required a therapeutic transforaminal epidural blood patch. Two minor complications occurred, both of which involved inadvertent puncture of a dorsal muscular arterial branch, without clinical sequelae. A fluoroscopy-guided curved-needle transforaminal approach is an effective technique for lumbar puncture in difficult cases, such as in this cohort of patients with spinal muscular atrophy and complete interlaminar osseous fusion undergoing intrathecal nusinersen injections.TFLPtransforaminal lumbar punctureSMAspinal muscular atrophy